PENGEMBANGAN BAHAN AJAR BERBASIS TEKNOLOGI INFORMASI PADA GURU SD MUHAMMDIYAH PANDES PLERET BANTUL - Muhammad Sholeh; Untung Joko Basuki (LPPM IST AKPRIND Yogyakarta, 2019)
The use of information technology-based teaching materials is now an option that teachers cannot abandon. The learning process not only relies on textbooks that can only display text and image narratives. By using the computer, the teaching materials that are delivered to the students can be displayed more interesting and equipped with images, photographs, video even animations. With the completeness of video-based facilities and animation, of course, the material delivered can be more interactive and expected for students to be more digesting the material presented. The challenges teachers face are how teachers can anticipate these developments and be able to develop teaching materials or training questions based on information technology. To provide insight to the teachers, especially the elementary school Muhammadiyah teachers in Pleret subdistrict, the Community dedication team AKPRIND provides mentoring and training of teaching materials and exam-based technology. Information. The training material is the development of teaching materials using video scribe and make exam questions with quiz creator application.